2011
DOI: 10.1007/s13524-011-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Marriage for Survival: A Review and Update

Abstract: The theory that marriage has protective effects for survival has itself lived for more than 100 years since Durkheim's groundbreaking study of suicide (Durkheim 1951 [1897]). Investigations of differences in this protective effect by gender, by age, and in contrast to different unmarried statuses, however, have yielded inconsistent conclusions. These investigations typically either use data in which marital status and other covariates are observed in cross-sectional surveys up to 10 years before mortality expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
321
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(376 citation statements)
references
References 64 publications
36
321
2
8
Order By: Relevance
“…11 Several studies have also shown that the risk of mortality in the general population is lower for married patients. [17][18][19] The mechanism for this survival advantage is unknown. It is possible that married patients have better social support and more financial resources than single patients, which can lead to improved compliance with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have also shown that the risk of mortality in the general population is lower for married patients. [17][18][19] The mechanism for this survival advantage is unknown. It is possible that married patients have better social support and more financial resources than single patients, which can lead to improved compliance with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the effect of marriage on survival broadly (Rendall et al 2011) found little or no differences between never married, separated/divorced, and widowed statuses. A study of lung cancer in Japan found no significant increased risk of death in widowed female lung cancer patients compared to married patients, and no significant increased risk of death for separated/divorced male or female patients compared to married patients although widowed males patients had increased risk of death (HR 1.7; 95% CI = 1.2-2.5) (Saito-Nakaya et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent and growing literature suggests that psychological factors and the presence or absence of social support may be an important factor influencing the course of cancer (Ikeda et al 2013;Pinquart & Duberstein 2010;Cassileth et al 1988;Rendall et al 2011); this has been shown to be especially strong for breast cancer (Falagas et al 2007;Nausheen et al 2009). There have been mixed results in the literature regarding the specific association of lung cancer survival and marital status.…”
Section: Introductionmentioning
confidence: 99%
“…The marriage selection effect (Goldman 1993) is the reduced likelihood that less healthy individuals will marry. Marriage is also found to be protective insofar as partners can help each other economically, emotionally, and in diverse aspects of everyday life (Rendall et al 2011). Lillard and Panis (1996) discuss adverse selection when unhealthy men tend to remarry in order to regain the protective support of marriage.…”
Section: Background and Objectivesmentioning
confidence: 99%